Analysis of the Surface Temperature and Energy Performance for the Double Paned Glazing Filled with Carbon Dioxide as an Insulating Gas - et.al, Sanghoon Baek (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background/Objectives: The purpose of this study is to develop a double glass infused with CO2 as a part of the work to resource greenhouse gases in buildings. Methods/Statistical analysis: In the case of analysis of the results, the analysis point was focused on January during the heating period with a large indoor/outdoor temperature difference. The amount of energy lost, and the amount of heating energy used in the room. In addition, details of the concept, characteristics, and heat transfer process of the CO2 double glass have been described in detail in the previous study and will be omitted in this paper. Findings: This study aims to analyze the insulating and energy performances for the double paned glazing filled with carbon dioxide (CO2) gas as one of works to utilize greenhouse gases in buildings . For this, double paned glazing with CO2, Air, Argon, and Krypton gases respectively apply to the building designed by the computer simulation program, and then, hourly surface temperatures in the indoor pane, hourly energy losses, and total energy consumption in the building are compared. The simulation programs are Therm & Window and EnergyPlus. The results revealed that the indoor surface temperatures of the glazing with CO2 gas are located between the glazing with Air and Krypton gases, and are similar to the glazing with Argon gas. In analysis of energy performance, it was shown that the building with CO2 glazing consumes heating energy at a similar level to the case of Argon gas. Improvements/Applications: The insulation and energy performance when CO2 gas was injected into the double glass was verified, and it was found that it exhibited similar performance to the existing Ar gas and thus has high potential as an insulating gas.